Borderline personality disorder and childhood maltreatment: a genome‐wide methylation analysis. (1st February 2015) - Prados, J.; Stenz, L.; Courtet, P.; Prada, P.; Nicastro, R.; Adouan, W.; Guillaume, S.; Olié, E.; Aubry, J.‐M.; Dayer, A.; Perroud, N.
Abstract : Early life adversity plays a critical role in the emergence of borderline personality disorder (BPD) and this could occur through epigenetic programming. In this perspective, we aimed to determine whether childhood maltreatment could durably modify epigenetic processes by the means of a whole‐genome methylation scan of BPD subjects. Using the Illumina Infinium® HumanMethylation450 BeadChip, global methylation status of DNA extracted from peripheral blood leucocytes was correlated to the severity of childhood maltreatment in 96 BPD subjects suffering from a high level of child adversity and 93 subjects suffering from major depressive disorder (MDD) and reporting a low rate of child maltreatment. Several CpGs within or near the following genes (IL17RA, miR124‐3, KCNQ2, EFNB1, OCA2, MFAP2, RPH3AL, WDR60, CST9L, EP400, A2ML1, NT5DC2, FAM163A and SPSB2) were found to be differently methylated, either in BPD compared with MDD or in relation to the severity of childhood maltreatment. A highly relevant biological result was observed for cg04927004 close to miR124‐3 that was significantly associated with BPD and severity of childhood maltreatment. miR124‐3 codes for a microRNA (miRNA) targeting several genes previously found to be associated with BPD such as NR3C1 . Our results highlight the potentially important role played by miRNAs in the etiology of neuropsychiatric disorders such as BPD and the usefulness of using methylome‐wide association studies to uncover such candidate genes. Moreover, they offer new understanding of the impact of maltreatments on biological processes leading to diseases and may ultimately result in the identification of relevant biomarkers. Abstract : This genome‐wide methylation analysis in borderline personality disorder highlights the potentially important role played by microRNAs in the etiology of neuropsychiatric disorders.